Review paperChancroid – clinical manifestations, recent epidemiology, diagnosis and treatment - Duś, Monika (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
Chancroid (ulcus molle) is a sexually transmitted disease (STD) caused by the fastidious Gram-negative streptobacillus Haemophilus ducreyi. It usually manifests as a painful ulcer on the genitalia. In 50 percent of untreated cases ulcerations are accompanied by inflammatory inguinal adenopathy. It is more commonly seen in men than in women, particularly uncircumcised males. Tropical and subtropical regions have the highest incidence of this disease. More frequent travel to countries where Haemophilus ducreyi is endemic may lead to spread of the infection in Europe and North America. The connection between genital ulcer diseases (GUD) and higher risk of HIV-1 infection contributes to the renewal of interest in chancroid and other STDs. The purpose of this paper is to review recent literature about the incidence of chancroid in developed countries and to present the latest information about epidemiology, clinical picture, diagnostics and treatment of Haemophilus ducreyi infection.